2016
DOI: 10.1002/acp.3293
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Running‐Man Emergency Exit Sign and Its Installed Location on Human Directional Choice

Abstract: Understanding the meaning of an emergency exit sign is essential for escaping from a building during a disaster. According to International Organization for Standardization 7010:2011, there are leftward and rightward running-man exit signs indicating the location of an exit door. However, there is neither an application rule regarding which direction the sign should point nor a rule for where it should be attached in the horizontal dimension. We examined the effect of the heading direction of the running man a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Research into technical assistant systems has demonstrated that they provide help during the early stages of evacuations through early warnings of danger, providing instructions for decision-making, and guiding evacuees to exit affected tunnel (Kim et al, 2016, Olander et al, 2017, Kinateder et al, 2019. For example, Heskestad (1999) reanalysed a Norwegian experiment and discovered that low location lighting provided correct decision-making between 70% and 80% regardless of whether it was electrically powered or photo luminescent.…”
Section: Introductionmentioning
confidence: 99%
“…Research into technical assistant systems has demonstrated that they provide help during the early stages of evacuations through early warnings of danger, providing instructions for decision-making, and guiding evacuees to exit affected tunnel (Kim et al, 2016, Olander et al, 2017, Kinateder et al, 2019. For example, Heskestad (1999) reanalysed a Norwegian experiment and discovered that low location lighting provided correct decision-making between 70% and 80% regardless of whether it was electrically powered or photo luminescent.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have used sensors to detect the locations 61 of fires and indicate a safe route using blinking signs (Yenumula et al, 62 2015). In addition, the traditional exit sign icon (i.e., a running person) may be oriented and located towards the direction of the optimal exit route in order to guide evacuations (Kim et al, 2016). Here, various designs for indicating incorrect or inefficient directions have also been tested.…”
Section: Intelligent Fire Evacuation Systemsmentioning
confidence: 99%
“…Based on visibility, this paper introduces a smart evacuation signage layout design method that can be adapted to different booth layout forms in the exhibition Evacuation signage plays the role of conveying evacuation guidance information in the exhibition space, and its effectiveness is influenced by both sign visibility and content readability. Currently, the legislation, standards, and related studies, such as the Design Code for Exhibition Building (JGJ 218-2010) and the Code for Fire Protection Design of Buildings (GB50016-2014), have primarily focused on sign text [10], graphics [11,12], color [13,14], size [15], brightness characteristics [16,17], and smart evacuation guidance systems [18,19] to solve the problem of the readability of evacuation signage, but not much research has been devoted to whether evacuation signage can be "seen". In practice, many evacuation signs are often set up formally, blindly, and arbitrarily, ignoring the relationship between booth layout and the visibility range of evacuation signage in the three-dimensional space.…”
Section: Introductionmentioning
confidence: 99%